Comparing lacustrine environments: The importance of the kind of habitat on the structure of fishes - de Castro, Reinaldo José; Henry, Raoul [UNESP]; Ferragut, Carla; Casartelli, Mayara (FapUNIFESP (SciELO), 2018)
Aim: Fish diversity in two lentic environments: a lake connected (Barbosa lake) to a river and an artificial reservoir (Ninfeias reservoir) were determined in the dry and rainy periods in 2015. We expected to find more diversity in the connected lake and greater abundance in the reservoir. Methods: Specimens were caught using gill nets. Moreover, environmental parameters such as temperature, electrical conductivity, pH, dissolved oxygen and water transparency were measured during the two periods. Results: 546 specimens were collected from 9 families, 12 genera and 15 species of the orders Characiformes, Siluriformes, Cichliformes and Gymnotiformes. Pimelodus maculatus was the most abundant species in the connected lake. Two species were caught from the reservoir: Geophagus brasiliensis and Hoplias malabaricus, the former being predominant. The dominant species in the studied environments corresponded to 48.71% of the total number of specimens. The ichthyofaunal composition from the lake showed a high richness of the order Characiformes (66.7%). Siluriformes and Gymnotiformes represented 13.3% each and the order Cichliformes only 6.7% of the total number of species. In the artificial reservoir, there was an equivalent contribution of Cichliformes and Characiformes. The diversity was higher in the lake (H’ = 2.05) and lower in the reservoir (H’ = 0.34). Significant differences (p<0.05) of diversity were found between the connected lake and the reservoir. The catch of fish was lower in the dry season (24.7%) than the rainy season (62.3%). The principal component analysis (PCA) showed segregation between the two environments and periods, which was due to the difference in water electrical conductivity. The prevalence of species of the orders Characiformes and Siluriformes follows the pattern found for the ichthyofauna in the Neotropical region. Conclusions: The analysis of distinct patterns of diversity and abundance of the ichthyofauna from the studied environments showed that the environment connected to the river has a high diversity when compared to the reservoir. The presence of aquatic macrophytes of different species may be a regulating factor in structuring the fish community of the lake connected to the river.
Comparando ambientes lacustres: A importância do tipo de habitat na estrutura de peixes
Keywords: Abundance; Assemblage structure; Connected lagoon; Fish; Shallow reservoir